2019
DOI: 10.1538/expanim.18-0053
|View full text |Cite
|
Sign up to set email alerts
|

Regional expression of tyrosinase in central catecholaminergic systems of colored mice

Abstract: A relationship between coat color and behavioral characteristics has been reported for numerous species. We previously indicated that particular behavioral traits contributing to the genotype at the agouti locus manifest only when possessing a wild-type allele at the albino (i.e., tyrosinase: Tyr) locus. The present study was performed to investigate tyrosinase expression with marked activity in central nervous systems. The whole brain of male B10 and B10-c mice, a B10 congenic strain of the albino locus from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In the case of overexpression of tyrosinase in astrocytes, this enzyme can also oxidize dopamine, since this type of glial cell can take up dopamine released during neurotransmission; (iii) the triggering agent of the neurodegenerative process in this preclinical model is not a neurotoxin that can be the target of new pharmacological drugs attempting to stop the degenerative process, but rather it is tyrosinase, which is not expressed in the human substantia nigra. However, there are some reports that suggest its expression in this tissue [ 60 ], but if it were true that tyrosinase is normally expressed in neuromelanin-containing dopaminergic neurons, the presence of the pigment would be observed from an early age in children. Several studies have indeed shown that tyrosinase is not present in the human substantia nigra, even using highly specific and sensitive mass spectroscopy [ 61 , 62 ] (Zucca et al, 2018; Tribl et al, 2007).…”
Section: Preclinical Model For Idiopathic Parkinson’s Diseasementioning
confidence: 99%
“…In the case of overexpression of tyrosinase in astrocytes, this enzyme can also oxidize dopamine, since this type of glial cell can take up dopamine released during neurotransmission; (iii) the triggering agent of the neurodegenerative process in this preclinical model is not a neurotoxin that can be the target of new pharmacological drugs attempting to stop the degenerative process, but rather it is tyrosinase, which is not expressed in the human substantia nigra. However, there are some reports that suggest its expression in this tissue [ 60 ], but if it were true that tyrosinase is normally expressed in neuromelanin-containing dopaminergic neurons, the presence of the pigment would be observed from an early age in children. Several studies have indeed shown that tyrosinase is not present in the human substantia nigra, even using highly specific and sensitive mass spectroscopy [ 61 , 62 ] (Zucca et al, 2018; Tribl et al, 2007).…”
Section: Preclinical Model For Idiopathic Parkinson’s Diseasementioning
confidence: 99%
“…Although the expression and enzymatic activity of tyrosinase have been detected in differentiated melanocytes distributed in the skin and retinal pigment epithelium, we and other researchers also reported tyrosinase enzymatic activity in the central nervous system, particularly in the midbrain substantia nigra of mammals [6–10]. Although the functional role of tyrosinase in the brain remains largely unknown, we have previously reported that tyrosinase activity prevented oxidative stress-induced protein damage in the mouse substantia nigra [11].…”
Section: Introductionmentioning
confidence: 97%